PJMHS 2022
DOI: 10.53350/pjmhs22169427
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study Combinition of Proton Pump Inhibitors with Prokinetics in Gerd

Abstract: Background: Gastroesophageal reflux disease (GERD), a fairly common ailment that has a negative influence on quality of life. 30- 40% of patients with GERD have an insufficient response to standard PPIs therapy. For subjects resistant to this PPI therapy, double the PPI dosage or switch to different PPIs, which may not be ideal. So, combination therapy with prokinetic agent will significantly improve GERD symptoms. Study Design: A prospective observational study. Place and Duration: In the Department of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, another study suggested that there may be no additional benefit of combining PPIs with prokinetics compared to PPI monotherapy in adult patients with overlapping functional dyspepsia and GERD, suggesting that PPI monotherapy alone may be sufficient as an initial treatment option [ 178 , 179 ]. Combining prokinetic agents and PPIs has been shown to improve GERD symptoms in individuals with high scores on the FSSG scale [ 180 ].…”
Section: Chitosan-based Nanoparticle-based Systems For Gerd Treatmentmentioning
confidence: 99%
“…However, another study suggested that there may be no additional benefit of combining PPIs with prokinetics compared to PPI monotherapy in adult patients with overlapping functional dyspepsia and GERD, suggesting that PPI monotherapy alone may be sufficient as an initial treatment option [ 178 , 179 ]. Combining prokinetic agents and PPIs has been shown to improve GERD symptoms in individuals with high scores on the FSSG scale [ 180 ].…”
Section: Chitosan-based Nanoparticle-based Systems For Gerd Treatmentmentioning
confidence: 99%